Factors Influencing Acute Exacerbation of Bronchial Asthma Among Children in Malaysia (International Journal of Child Health and Nutrition, 2014)
The aim of this study was to determine the factors influencing acute exacerbation of bronchial asthma among children in Malaysia. A cross-sectional study was done to identify the factors influencing acute exacerbation of asthma in the University Malaya Medical Centre. In this study 103 known asthmatic children between the ages of 2 to 12 years were analysed. Among the children, 60% had a family history of asthma, 39% allergic rhinitis and only 17% eczema. The main complaints were coryza (84%) and shortness of breath (88%). Majority of the patients were treated as out-patient (58%) and only two were admitted in Intensive Care Unit. The factors that were significantly associated with mild exacerbation compared to a moderate to severe exacerbation was well-controlled asthmatic, good compliance to medications and those who had regular follow up.